The poet and his world: critical essays on Rabindranath Tagore - Quayum, Mohammad Abdul (Orient BlackSwan (Orient Longman), 2011)
Seventy years after his death, Tagore's genius still provides ample scope for critical analyses of his writings, especially in the English language and outside the subcontinent.